The Influence of Price Discount, Hedonic Shopping Motivation, and Shopping Lifestyle on Impulse Buying at RJ Galery Store in Bengkulu City - Nengsi, Elva Gustiaeni; Yulinda, Ade Tiara (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to analyze the influence of price discounts, hedonic shopping motivation, and shopping lifestyle on impulse buying at the RJ Galery Store in Bengkulu City. This study uses a quantitative approach with data collection techniques through questionnaires to 190 respondents from Bengkulu City. The data analysis technique used is multiple linear regression to test the influence of each independent variable on the dependent variable. The results of the analysis indicate that partially, price discounts, hedonic shopping motivation, and shopping lifestyle have a positive and significant effect on impulse buying. Attractive price discounts can trigger impulsive shopping behavior because they are seen as an opportunity to buy at a lower price. Hedonic shopping motivation also contributes due to the emotional drive of consumers who seek pleasure when shopping. In addition, shopping lifestyle that reflects consumption patterns following trends also plays an important role in influencing spontaneous purchasing decisions. Simultaneously, these three variables have a significant influence on impulse buying. These findings imply that retail businesses, especially in the fashion sector, need to design marketing strategies that consider the psychological aspects and lifestyle of consumers to encourage profitable unplanned purchases.